Texas, a modern history - McComb, David G. (Bridwell Texas history series., 2010)
Covers the Battle of the Alamo, the Civil War, cattle trails, oil discovery, and the growth of cities, changes in politics, the Great Depression, World War II, recreation, economic expansion, and recession. Features the post-World War II rise of the Republican Party in Texas and the evolution of the state from rural to urban.